Exploring the link between port throughput and economic activity: Some comments on space- and time-related issues - Thomas Vanoutrive (European Regional Science Association (ERSA), 2010)
The link between economic activity and freight transport is a classic issue in regional science. A subtopic is the impact of economic activity on the demand for maritime transport through ports. Understanding this relationship contributes to a better understanding of the dynamics of port throughput, which is important for infrastructure planning and other strategic decisions. This paper focuses on the port of Antwerp (Belgium) and applies some different methods to model port throughput. Moreover, we discuss the differences between commodity groups and the impact of neighbouring ports on the model results. As a result, the results will also be relevant for other ports.
Keywords: 330